Coupling of T161 and T14 phosphorylations protects cyclin B–CDK1 from premature activation - Coulonval, Katia (The American Society for Cell Biology, 2011)
Mitosis is triggered by the abrupt dephosphorylation of inhibitory Y15 and T14 residues of cyclin B1–bound cyclin-dependent kinase (CDK)1 that is also phosphorylated at T161 in its activation loop. The sequence of events leading to the accumulation of fully phosphorylated cyclin B1–CDK1 complexes remains unclear. Two-dimensional gel electrophoresis allowed us to determine whether T14, Y15, and T161 phosphorylations occur on same CDK1 molecules and to characterize the physiological occurrence of their seven phosphorylation combinations. Intriguingly, in cyclin B1–CDK1, the activating T161 phosphorylation never occurred without the T14 phosphorylation. This strict association could not be uncoupled by a substantial reduction of T14 phosphorylation in response to Myt1 knockdown, suggesting some causal relationship. However, T14 phosphorylation was not directly required for T161 phosphorylation, because Myt1 knockdown did uncouple these phosphorylations when leptomycin B prevented cyclin B1–CDK1 complexes from accumulating in cytoplasm. The coupling mechanism therefore depended on unperturbed cyclin B1–CDK1 traffic. The unexpected observation that the activating phosphorylation of cyclin B1–CDK1 was tightly coupled to its T14 phosphorylation, but not Y15 phosphorylation, suggests a mechanism that prevents premature activation by constitutively active CDK-activating kinase. This explained the opposite effects of reduced expression of Myt1 and Wee1, with only the latter inducing catastrophic mitoses.